ABOUT THE PROBLEM OF STUDYING DIFFICULT TOPICS IN THE COURSE OF MATHEMATICS 4 CLASSES OF UPDATED EDUCATION CONTENTS OF THE REPUBLIC OF KAZAKHSTAN - Akpaeva А.Б.; Lebedeva Л.А.; Мynzhasarova М.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
It is considered some issues of studying sophisticated themes in the 4th grade mathematics course. The analysis of the content of the program and its implementation in the educational-methodical complex "Mathematics" is discussed. The updated content of the mathematical education of elementary schools has significant differences from previous generations of programs. A distinctive feature of the 4th grade syllabus is that the material is not evenly distributed throughout the half-year periods, and several difficult themes not previously studied in elementary school are also included, and the authors created an exercise system that implements an activity-based approach to learning.